Diseño de joyería contemporánea a partir de los recursos visuales de la comunidad de Salasaka - Haro Robles, Lady Juliana (2024)
The study of "Contemporary jewelry design from the visual resources of the Salasaka community" seeks to merge the current jewelry designs with the visual resources of Salasaka, aims to develop a line of jewelry especially highlighting the use of the Chakana. The study started from the ornamentation used by the Salasaka community, which includes the use of stones, although it is not strictly considered jewelry. In addition, the community does not make adequate use or representation of their visual resources, which puts the preservation of their designs at risk. On the other hand, foreign fashion has had a great influence on the Ambateño and Ecuadorian community, since they prefer designs from outside our country, leaving aside their designs representative of the ancestral cultures of our country. To gather information about the visual resources that the community has represented in tapestries, and the analysis of the forms with their meanings; a direct observation, interviews with local artisans and the analysis of the products manufactured by the community and its great cultural relevance were carried out. The research revealed that it possesses a wide variety of symbols that reflect the Salasaka cultural heritage, including representations such as mystical animals and geometric shapes. Among these symbols, the most important for the community were identified. One of them; La Chakana, as a central visual resource, was fundamental to the development of the jewelry collection. The collection not only offers aesthetically attractive products, but also the valorization of these resources. The Chakana, which represents a cross, symbolizes the calendar used for planting and encapsulates the geometric composition of the Salasaka culture. It is the union between the earth and the sky. For the application of the Chakana, a shape analysis was developed using meshes and supermodules, to generate the shapes from which the jewelry design will be developed. The contributions of this work are significant both for the Salasaka community and for the field of contemporary jewelry design. On the one hand, cultural identity is strengthened and on the other hand, jewelry design is enriched with the inclusion of authentic cultural elements, such as the Chakana, creating unique and meaningful pieces.